Optical and thermal properties of laser-ablated platinum nanoparticles graphene oxide composite - Sadrolhosseini, Amir Reza; Habibiasr, Mina; Shafie, Suhaidi; Soleimani, Hassan; Lim, Hong Ngee (MDPI, 2019)
Platinum nanoparticles were synthesized in graphene oxide aqueous solution using a laser ablation technique to investigate the effect of optical linear, nonlinear and thermal properties of platinum-graphene oxide nanocomposite solution. The samples were prepared with different ablation times. The platinum nanoparticles that formed a spherical shape on the surface of graphene oxide solution were authenticated using UV-visible spectrum and transmission electron microscopy patterns. The particle size decreased with increasing ablation time, and the concentration and volume fraction of samples were increased. To obtain the optical linear, nonlinear and thermal properties of platinum-graphene oxide nanocomposite solution, UV-visible spectroscopy, Z-scan, thermal lens and photoacoustic techniques were used. Consequently, the linear and nonlinear refractive indices increased with an increase in the volume fraction of platinum nanoparticles. It was observed from the spatial self-phase modulation patterns that, the optical nonlinear property of the graphene oxide was enhanced in the presence of platinum nanoparticles, and the nonlinearity increased with an increase in the volume fraction of platinum nanoparticles inside the graphene oxide solution. The thermal diffusivity and thermal effusivity of platinum nanoparticles graphene oxide were measured using a thermal lens and photoacoustic methods, respectively. The thermal diffusivity and thermal effusivity of samples were in the range of 0.0341 × 10−5 m2/s to 0.1223 × 10−5 m2/s and 0.163 W s1/2 cm−2 K−1 to 0.3192 W s1/2 cm−2 K−1, respectively. Consequently, the platinum enhanced the optical and thermal properties of graphene oxide.